No Difference in Sympathetic Responses to Auditory, Visual, and Combined Stimuli - Christensen, Erica; D’Amato, Joe; Patel, Gina; Prasad, Aisha; Pynnonen, Eric; Waier, Kelsey (Journal of Advanced Student Sciences (JASS), 2014)
The sympathetic nervous system, a branch of the autonomic nervous system, is activated in response to stressful stimuli. The purpose of this experiment was to determine whether audio or visual stimuli work in tandem to elicit a greater response, or whether they work in an unrelated fashion. The experimenters hypothesized that auditory and visual stimuli combined would evoke a greater sympathetic response than the summation of the responses to auditory stimuli only and visual stimuli only. The hypothesis was tested by exposing the subjects to an audio track, a muted movie, or both combined, each with a brief startling stimulus. The research group recorded heart rate, GSR, and respiratory rates and calculated the percent change between the stimulated response and the baseline values for the subject, and performed subsequent tests between experimental populations. The results did not show a statistically significant response between solitary or combined stimuli, due to the large variance in the population.
An article that appeared in JASS, issue 2014
Keywords: sympathetic nervous system; auditory; visual; startle stimulus; synergy; respiratory rate; heart rate; GSR; audio/visual; fear response